Oil Revenue, Public Spending, Gross Domestic Product and Employment in Saudi Arabia - Alkhateeb, Tarek Tawfik Yousef; Sultan, Zafar Ahmad; Mahmood, Haider (International Journal of Energy Economics and Policy, 2017)
Saudi Arabia has largest oil production and exports in the world. Oil’s revenues form the backbone of the economy and it is also a main source of government revenue which determines the major economic activities in the country. This paper has investigated the relationship between oil revenue and employment level by augmenting two more variables like GDP and public spending for a period 1991-2016. We find that there is a cointegration among oil revenue, GDP, public spending and level of employment in Saudi Arabia. The VECM results show that oil revenue and public spending are causing the level of employment in Saudi Arabia. This study observes that declining oil price and its consequent impact on oil revenue may pose a challenge to the economy unless it diversifies its economic base and reduces its dependence on oil sector. Therefore, we recommend the government to reduce oil dependency to improve employment level. Keywords: Oil Revenue, Employment, Causality JEL Classifications: C22, E24, H50